Effect of wind and altitude on record performance in foot races, pole vault, and long jump - Frohlich, C. (American Journal of Physics, 1985)
Using only elementary physics, one can estimate the effect of wind and altitude on performance in several track and field events. Experiments have shown that the power lost to aerodynamic drag forces is about a tenth of the total power expended in running at sprint speeds. From this observation one can calculate the effect of wind or of air density changes on sprinting speed. In pole vaulting, the sprinter converts his kinetic energy into potential energy to clear the bar. In long jumping, he is a projectile, but he is prevented from reaching his optimum distance expected for his initial velocity by the height which he can attain during his jump. For each of these events, performance in moderate winds of 2.0 m/s or at altitudes comparable to Mexico City differ by several percent from performances at sea level or in still air. In longer running races and in bicycle races, aerodynamic forces play an important role in racing strategy. However, since the athletes perform in groups it is difficult to calculate the effect on individual performances.